Wawasan Kebangsaan Santri Milenial (Studi Kasus Di Pondok Pesantren Roudhotus Sholihin, Demak) - Wicaksono, Nicolas Eka Novian; Sugiyana, Fx.; Krismawanto, Hieronimus Heri; Aprianto, Dicky (Faidatuna, 2023)
This Research Aims To Know, Describe, And Analyze The Role Of Islamic Boarding Schools In Implementing The National Insight Of Millennial Generation Santri In Traditional Islamic Boarding Schools As A Resolution Of Globalization Turbulence. The method used in this research is qualitative. Data Collection Techniques Using Observations And Interviews. The research location is the Roudhotus Sholihin Sayung Islamic Boarding School, Demak. The results of this research are that these traditional Islamic boarding school students have a national outlook which is marked by their knowledge of the position of Pancasila as the basis of the state. Santri are also able to practice the precepts of Pancasila, have knowledge of the concept and meaning of Bhinneka Tunggal Ika, respect differences, use the Indonesian language, respect the flag, maintain national integrity, and counteract radicalism and terrorism. The Role of Islamic Boarding Schools in Implementing National Insights Is By Carrying out the Rite of Independence Commemoration of the Republic of Indonesia, Equitable Distribution of Student Bedrooms, Use of the Indonesian Language, Implementation of Grave Pilgrimage, and Commemoration of Religious Holidays. The Islamic Boarding School's Efforts in Maintaining the Republic of Indonesia and Building the National Spirit Are Literacy in Communication Media, Reviving the Islamic Boarding School Rules, Organizing Bahsul Masail, and Socializing the Islamic Boarding School's Vision and Mission.